2005
DOI: 10.1161/01.hyp.0000174593.88899.68
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Stimulates Collagen Gene Expression and Synthesis Via Activation of ERK1/2 in Rat Renal Fibroblasts

Abstract: Abstract-Recently, we demonstrated that in rats treated chronically with aldosterone and salt, severe tubulointerstitial fibrosis is associated with the activation of mitogen-activated protein kinases (MAPKs), including extracellular signal-regulated kinases (ERK1/2). Here, we investigated whether aldosterone stimulates collagen synthesis via ERK1/2-dependent pathways in cultured rat renal fibroblasts. Gene expression of mineralocorticoid receptor (MR) and types I, II, III, and IV collagen was measured by real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
115
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(129 citation statements)
references
References 37 publications
11
115
1
2
Order By: Relevance
“…We recently found that aldosterone stimulates reactive oxygen species production (15) and induces cell proliferation (16) or deformation (16) in cultured glomerular mesangial cells. In addition, aldosterone stimulated collagen synthesis in cultured renal fibroblasts (17). Collectively, these data suggest that aldosterone has deleterious effects on the kidney that cannot be explained simply by BP changes.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…We recently found that aldosterone stimulates reactive oxygen species production (15) and induces cell proliferation (16) or deformation (16) in cultured glomerular mesangial cells. In addition, aldosterone stimulated collagen synthesis in cultured renal fibroblasts (17). Collectively, these data suggest that aldosterone has deleterious effects on the kidney that cannot be explained simply by BP changes.…”
mentioning
confidence: 76%
“…␤ 1 , CTGF, and monocyte chemoattractant protein-1 (MCP-1) were analyzed by real-time PCR using an ABI Prism 7000 Sequence Detection System (Applied Biosystems, Foster City, CA) (17,33,34). The oligonucleotide primer sequences of GAPDH and types I and III collagen were reported previously (17,33).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Promoter activity was determined by a GloMax 96 Microplate Luminometer (Promega) using a Dual-Glo Luciferase Assay System (Promega). As for the concentration of Aldo 10 À7 M, in the promoter assay, we referred other investigators' studies 23 …”
Section: Construction Of the Opn Gene Promotersmentioning
confidence: 99%
“…The most important downstream factors mediating the ECM synthesis of TGF-β1 are mitogen-activated protein kinase (MAPK) signals, including extracellular signal-regulated kinase (ERK), p38 MAP kinase and c-jun N-terminal kinase (JNK). ERK mediates TGF-β1-induced synthesis of plasminogen activator inhibitor type I (6), CTGF (7) and aldsterone-stimulated collagen synthesis (8). ERK is also involved in the ECM synthesis in diabetic rats (9).…”
Section: Introductionmentioning
confidence: 99%